Manajemen Strategi Badan Kesatuan Bangsa dan Politik Kabupaten Solok 2025–2030 - Riyosnal Putra; Syafwandi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
The National Unity and Politics Agency (Kesbangpol) of Solok Regency plays a strategic role in maintaining national resilience and political stability at the regional level. This study aims to formulate a medium-term strategy (2025–2030) through a SWOT analysis and Balanced Scorecard (BSC) approach. The analysis results indicate that Kesbangpol has strengths in terms of human resources who understand local political issues and partnerships with security agencies, but faces limitations in terms of budget and technology utilization. Opportunities include public support for the Unitary State of the Republic of Indonesia (NKRI) and trends toward cross-sector collaboration, while threats include radicalism, political polarization, and hoaxes. The strategies formulated include institutional strengthening, service digitalization, national awareness campaigns, radicalism prevention, regional policy synergy, and political resilience evaluation. These findings are expected to serve as a reference for Kesbangpol's strategic planning to achieve conducive political stability.